Qualidade de linguiça frescal de frango produzida com peito amadeirado (Wooden Breast) - Rocha, Thayse Cavalcante da (2018)
Wooden Breast (WB) is an anomaly that occurs in poultry characterized by changes in the Pectoralis major, such as pale, swollen areas and hardened areas, either partial or total. WB is sent to the production of products of lower commercial value, due its sensorial rejection by the consumers. The aim of this work was to evaluate the effects of the use of WB on the preparation of fresh sausage, characterizing its technological properties and physical-chemical and sensorial parameters during storage under commercial freezing at -20 °C for 180 days. It was elaborated three types of fresh sausages: using 100% Normal chicken breast (N), 100% WB and 50% N and 50% WB (N + WB). WB meat presented higher pH, L* value, moisture content, cooking losses, shear force (SF), hardness, chewiness, adhesiveness and gumminess, when compared with N breast. On the other hand, water holding capacity (WHC) and protein content were higher in N. Fresh sausages produced with 100% WB and 100% N presented close values of CRA, a* and b* values, protein content and TBARS; and these differed from the mixed formulation (N + WB). The ADQ did not presented sensorial differences among the three formulations of fresh sausages. It was observed a decrease in WHC and in a* and b* values for the fresh sausages throughout the storage under commercial freezing. WB fresh sausages presented greater SF, hardness chewiness, cohesiveness, adhesiveness and resilience during the 180 days; besides a more pronounced reduction in WHC. Regardless of the formulation, there was an increase in TBARS values, which exceeded the limit of rancid detection. The results indicate that WB fresh sausages present greater lipid oxidation stability and can be commercially stored at -20°C for 190 days or 200 days when formulated with N + WB. N fresh sausages can be stored for up to 171 days under the conditions of the present study. The results indicate that the WB meat can be used in the industry to prepare processed products of the fresh type (sausage), whether or not combined with N meat. The elaboration of fresh chicken sausage with WB meat is a viable alternative for the poultry industry to reduce the economic losses conferred by this myopathy.